Finding the Community's Voice: Community-Based Participatory Research in Three Iowa Counties - Tera R. Hurt; Soyoung Park; Margaret C. O'Connor; Chanelle Murtha; Maya Bartel (The University of Alabama, 2022)
Engaging all Iowans in building a stronger state, preparing for a thriving future, and solving contemporary problems in research, education, and extension are central to the mission and vision of Iowa State University Extension and Outreach (EO). Achieving these goals will hinge upon EO's ability to innovate and respond to the needs and interests of Iowa's diverse residents. Similar to other rural states, the composition of Iowa's population is evolving in terms of race, nationality, economics, and education. The identities of EO staff do not reflect the communities EO is committed to serving; therefore, programming and activities may lack cultural relevance. In three small studies, Iowa State faculty and research assistants, EO staff, and community consultants (CCs) collaboratively organized local "study circles" and "action forums" in an effort to better understand underrepresented families' needs in three Iowa counties. The team recruited 98 adults and youth to participate in these group discussions. Often, participants were not aware of EO's mission, logo, or programs and services. Residents offered ideas for fostering familiarity, trust, and connection. CCs also listened to residents' barriers to engagement, such as program formats and topics, and documented useful resources to enhance accessibility. Participants shared ideas for programs that they would be motivated to engage in. In this article, the authors outline connections to prior work, recommendations, and limitations.